PIPELINE MULTIPLIER OF POLYNOMIALS MODULO WITH ANALYSIS OF HIGH-ORDER BITS OF THE MULTIPLIER - Kalimoldayev Maksat,; Tynymbayev Sakhybay,; Ibraimov Margulan,; Magzom Miras,; Kozhagulov Yeldos,; Namazbayev Timur, (Scientific Journal of Pedagogy and Economics, 2020)
Among public-key cryptosystems, cryptosystems built on the basis of a polynomial system of residual classes are special. Because in these systems, arithmetic operations are performed at high speed. There are many algorithms for encrypting and decrypting data presented in the form of polynomials. The paper considers data encryption based on the multiplication of polynomials modulo irreducible polynomials. In such a multiplier, the binary image of a multiply polynomial can serve as a fragment of encrypted text. The binary image of the multiplier polynomial is the secret key and the binary representation of the irreducible polynomial is the module. Existing sequential polynomial multipliers and single-cycle matrix polynomial multipliers modulo do not provide the speed required by the encryption block. The paper considers the possibility of multiplying polynomials modulo on a Pipeline in which architectural techniques are laid in order to increase computing performance. In the conclusion of the work, the time gain of the multiplication modulo is shown by the example of the multiplication of five triples of polynomials. Verilog language was used to describe the scheme of the Pipeline multiplier. Used FPGA Artix-7 from Xilinx companies. The developed Pipeline multiplier can be used for cryptosystems based on a polynomial system of residual classes, which can be implemented in hardware or software.